Unfolding the concept of a TMT-diversification strategy fit. Issue 3 (8th June 2015) - Weiss, Martin; Schneider, Dirk; Lebid, Jekaterina
Abstract : Purpose: – This paper aims to develop a conceptual foundation of a fit between top management teams (TMTs) and their company's corporate strategy. The authors fortify the importance of the concept of fit if the impact of upper echelons on organizational performance is trying to be explained. Yet, a constitutive concept of fit for the corporate strategy, a particularly important dimension of strategy, was previously neglected. Design/methodology/approach: – In a conceptual/theoretical approach, the authors selected demographic managerial characteristics from previous empirical studies from the research stream on upper echelons and combined them with other promising characteristics. To analyze them in respect to the requirements of low and highly diversified companies, the authors applied the concept of the dominant logic, an important theory in the field of corporate strategy. Findings: – The authors establish two distinct profiles of TMT members for low and high degrees of diversification and provide guidance on how to measure the TMT-corporate strategy fit – for individual TMT members and for the entire TMT – as a degree of fit on a ratio scale. Originality/value: – This work constitutes the first exhaustive concept of a TMT-corporate strategy fit. It provides a profound research foundation for scholars in the field of TMTs and the upper echelons theory as well as a promising and complementary perspective for practitioners when assessing their TMT composition.